Human activities and their awareness in the existence of Bagendit Lake as a tourism site, Garut West Java - Surtikanti, Hertien Koosbandiah; Soemarwoto, Rini; Surakusumah, Wahyu; Nilawati, Tina Safaria; Putra, Muhammad Naufal Nugraha (Institute of Advance Science, Social, and Sustainable Future, 2024)
Background: Bagendit Lake is a tourist lake located in Garut (West Java) and has experienced a decline in water quality. This research was conducted in settlements around Bagendit Lake with the aim of studying human activities and the level of concern for the existence of Bagendit Lake. Method: Mix method (Quantitative and Qualitative) was used in this study to collect data about the activities, knowledge education and environmental ethics of the community. The data collection technique was carried out by purposive sampling involving 40 respondents aged between 18-60 years. Data were obtained by conducting field observations, interviews, questionnaires and document recording. Findings: The results showed that the community received environmental knowledge education from schools (54%) and parents (46%). Surprisingly, as many as 93% of respondents stated that they played an active role in preserving the Bagendit Lake. However, various activities (such as tourism, fisheries, agriculture and settlements) have resulted in environmental damage to Bagendit Lake. It can be concluded that the level of knowledge and public awareness about the impact of activities on the environment has not been maximized. It is necessary to support the local government's role in implementing environmental improvement and conservation.